Early immune responses and development of pathogenesis of avian infectious bronchitis viruses with different virulence profiles - Okino, Cintia Hiromi; Mores, Marcos Antônio Zanella; Trevisol, Iara Maria; Coldebella, Arlei; Montassier, Hélio José [UNESP]; Brentano, Liana (Public Library of Science (PLoS), 2017)
Avian infectious bronchitis virus (IBV) primarily replicates in epithelial cells of the upper respiratory tract of chickens, inducing both morphological and immune modulatory changes. However, the association between the local immune responses induced by IBV and the mechanisms of pathogenesis has not yet been completely elucidated. This study compared the expression profile of genes related to immune responses in tracheal samples after challenge with two Brazilian field isolates (A and B) of IBV from the same genotype, associating these responses with viral replication and with pathological changes in trachea and kidney. We detected a suppressive effect on the early activation of TLR7 pathway, followed by lower expression levels of inflammatory related genes induced by challenge with the IBV B isolate when compared to the challenge with to the IBV A isolate. Cell-mediated immune (CMI) related genes presented also lower levels of expression in tracheal samples from birds challenged with B isolate at 1dpi. Increased viral load and a higher percentage of birds with relevant lesions were observed in both tracheal and renal samples from chickens exposed to challenge with IBV B isolate. This differential pattern of early immune responses developed after challenge with IBV B isolate, related to the downregulation of TLR7, leading to insufficient pro-inflammatory response and lower CMI responses, seem to have an association with a most severe renal lesion and an enhanced capability of replication of this isolate in chicken.